2020
DOI: 10.1111/his.14234
|View full text |Cite
|
Sign up to set email alerts
|

A method to obtain reproducible Ki‐67 indices in lung adenocarcinoma

Abstract: Aims Proliferative activity, evaluated from the Ki‐67 index, is a strong prognostic factor in lung adenocarcinoma (LADC). Here, we optimised a procedure to measure the Ki‐67 index and establish the best cut‐off value. Methods and results We examined 342 stage I LADCs for the immunohistochemical expression of Ki‐67 using different antibodies, MIB1 and SP6. The results revealed the superior specificity of SP6; therefore, SP6 was used in subsequent analyses. Slides were scanned with a virtual slide system. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Currently, the Ki-67 index is commonly regarded as a useful biomarker in clinical practice for predicting tumor cell proliferation, invasiveness, and prognosis and provides significant value in early lung cancer diagnosis and treatment assessment [ 21 , 22 ]. Recent research findings indicate that a Ki-67 index of 0.10–0.15 is a pivotal threshold for the proliferative activity of lung adenocarcinoma [ 20 ], suggesting a turning point toward higher tumor grades. Therefore, in this study, the Ki-67 threshold was set to 0.15 to categorize high and low expression levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the Ki-67 index is commonly regarded as a useful biomarker in clinical practice for predicting tumor cell proliferation, invasiveness, and prognosis and provides significant value in early lung cancer diagnosis and treatment assessment [ 21 , 22 ]. Recent research findings indicate that a Ki-67 index of 0.10–0.15 is a pivotal threshold for the proliferative activity of lung adenocarcinoma [ 20 ], suggesting a turning point toward higher tumor grades. Therefore, in this study, the Ki-67 threshold was set to 0.15 to categorize high and low expression levels.…”
Section: Discussionmentioning
confidence: 99%
“…The average percentage of positive cells among the total number of cells was quantitatively analyzed using the Ki-67 PI. The patients were categorized according to the Ki-67 labeling index (LI), with high and low Ki-67 LI defined as Ki-67 PI ≥ 15% and < 15%, respectively [ 20 ]. All pathological diagnoses were independently made by two pathologists.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the overall survival (OS) and disease-free survival (DFS) of patients with high Ki-67 expression are shorter than those with low Ki-67 expression (5)(6)(7). Previous studies have identified the Ki-67 labeling index as a strong prognostic biomarker for lung adenocarcinoma (8,9). Yamashita et al found that Ki-67 can be used as an indicator of recurrence of lung cancer after resection (10), and the level of its positive expression is closely related to the differentiation degree, lymph node metastasis, and other factors of lung cancer (8,11).…”
Section: Introductionmentioning
confidence: 99%